Cystinuria: A rare cause of bladder stone - Babu, Amalu Marutholil; Radhakrishnan, Radhika Chemmangattu; Uthup, Susan; Vasudevan, Beena Sushamma (Indian Journal of Case Reports, 2024)
Cystinuria is an inherited metabolic disorder progressing with recurrent kidney stones due to impaired reabsorption of dibasic amino acids and arises from mutations in the SLC3A1 and SLC7A9 on chromosome 2. Here, we present the case of a 1-year 10-month-old male child with recurrent episodes of urinary tract infections. On evaluation, duplex kidneys and a large bladder calculus were found which was surgically managed. Stone analysis and the genetic study were suggestive of cystinuria.